Dansk i hverdagen : – på vej mod en læringsinfrastruktur - Ø. Borg, Kamilla; B. Juhl, Niclas; D. Mathiasen, Ditte; H. Petersen, Carsten; Wagner, Johannes (Sprogforum. Tidsskrift for sprog- og kulturpædagogik, 2022)
Resumé